2014
DOI: 10.1016/j.vaccine.2013.08.076
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of rubella in the cord blood of pregnant women and congenital rubella incidence in Nha Trang, Vietnam

Abstract: To investigate susceptibility to and factors associated with rubella infection among pregnant mothers and to estimate the burden of congenital rubella infection (CRI) in Vietnam where rubella-containing vaccine (RCV) is not included in the routine immunization programme, we conducted a prospective cohort study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 13 publications
3
39
0
Order By: Relevance
“…The number of CRS cases in this study was comparable to the findings of previous epidemic reports from Oman, Ghana, Panama, and Russia (0.7, 0.8, 2.2, and 3.5 per 1000 live births during epidemics, respectively), 21,[24][25][26] and a CRS incidence of 2.3 (95% CI, 2.1-2.6) cases per 1000 live births in Vietnam estimated by modeling. 6 Unfortunately, hemodynamic status in each patient was not precisely recorded. Heart rates, respiratory rates, and oxygen saturation were recorded only at enrollment.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The number of CRS cases in this study was comparable to the findings of previous epidemic reports from Oman, Ghana, Panama, and Russia (0.7, 0.8, 2.2, and 3.5 per 1000 live births during epidemics, respectively), 21,[24][25][26] and a CRS incidence of 2.3 (95% CI, 2.1-2.6) cases per 1000 live births in Vietnam estimated by modeling. 6 Unfortunately, hemodynamic status in each patient was not precisely recorded. Heart rates, respiratory rates, and oxygen saturation were recorded only at enrollment.…”
Section: Figurementioning
confidence: 99%
“…We found that 29% (95% confidence interval [CI], 27%-31%) of enrolled pregnant females were rubellaspecific immunoglobulin G (IgG) antibodynegative and susceptible to rubella. 6 After that study was conducted, a large-scale rubella outbreak occurred between January and July 2011 throughout Vietnam (H.T.N. et al, unpublished observations), and many CRS cases emerged.…”
mentioning
confidence: 99%
“…However, infection with rubella virus in the first trimester of pregnancy may lead to miscarriage, stillbirth or a child born with congenital rubella syndrome (CRS). CRS is one of the greatest risks to newborn infants and may entail a variety of birth defects, such as sensor-ineural deafness, cataracts, and cardiac defects (1,2). Therefore, in 2000, the World Health Organization (WHO) recommended the use of the rubella-containing vaccine (RCV) in all national childhood immunization schedules to prevent congenital rubella infection, including CRS (3).…”
Section: Introductionmentioning
confidence: 99%
“…The access of microorganisms to the embryo before parturition causes the inflammatory response syndrome of the fetus against producing microbial products leading to premature labor. The consequences are multiple organ dysfunction syndrome (MODS) in the embryo and an increase in the mortality rate of the fetus (9). The results of this study showed that viral and parasitic bodies (Cytomegalovirus, Toxoplasma, and Rubella) are significantly evident and available in the blood serum of women.…”
Section: Discussionmentioning
confidence: 83%
“…The virus has the ability to transfer from placenta to fetus, and the risk of infecting the fetus depends on the age of the fetus when the mother is infected. The risk of abnormalities in the fetus in the first 12 weeks of pregnancy is 85% and after 16 weeks, it reaches the lowest point (9,10).…”
Section: Introductionmentioning
confidence: 99%